Predictive Ability At The Level Of Performance Of Sports Management In Terms Of Information Systems In Sports Institutions - Bellila , Zakarya; Mezghiche , Imene (sports creativity, 2025)
This study aimed to reach the predictive ability of the level of performance sports management in terms of information systems in sports institutions, The researchers used the descriptive method in its correlative and analytical methods, The sample of the study included (35) administrators, The researchers used questionnaire as a tool for study, SPSS 23 programme was used to calculate a set of statistical equations, Finally, a predictive equation was drawn up showing the percentage of information systems contribution to the performance of sports management , Therefore, the researchers recommended the need to pay attention to the technological and information aspect and to emphasize the importance of information systems and to work on their development and development in sports institutions